Efisiensi Penataan Daun Tembakau Rajang Pada Usaha Tani Jatiguwi Dengan Mesin Nganjang dan training pengenalan IPTEK (Mekanika, motor listrik, kontrol elektronika) - Setiawan, Budhy; Wakidah, Riska Nur; Widjanarko (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
Tobacco is an important commodity for the economy and livelihoods of farmers in Indonesia. Factors that influence the success of tobacco cultivation include climate, agricultural practices, and technology. East Java Province, as a major producer, contributed 49.04% of total national production in 2020. The quality of tobacco produced affects farmers' income and market prices, with global economic dynamics also influencing. The tobacco production process involves several steps, including classification, processing, and marketing. The implementation of this community service focuses on the processing process, namely Nganjang (arranging chopped tobacco leaves on the rigen). The development was carried out with an automatic nganjang machine to increase the efficiency of the tobacco leaf processing process in Jatiguwi Village, Malang Regency. A field survey was conducted to understand the needs of partners, namely KUB Makmur Barokah. Previous partners experienced obstacles in the manual nganjang process, namely the human resources required were quite a lot while regeneration was almost non-existent. So a machine is needed that is designed to be able to speed up the process and reduce the need for labor. The results of the Community Service activities show that the nganjang machine can work well and get a positive response from partners.